EU Task Force on Rail Infrastructure Charging. Summary Findings on Best Practice in Marginal Cost Pricing - Thomas, John; Dionori, Francesco; Foster, Adrian (European Journal of Transport and Infrastructure Research, 2003)
This paper sets out alternative best practice approaches to marginal cost pricing of rail infrastructure adopted in a number of EU Member States. It draws on the findings of a report submitted to the European Commission in June 2002 and provides a summary of two different approaches to the adoption of marginal cost pricing. The Swedish/Finnish approach uses econometric modelling to estimate marginal wear and tear costs whereas the UK model first provides a top-down estimate of the aggregate level of variable costs across the network and then uses relationships between vehicle characteristics and wear and tear costs to allocate the aggregate level of variable costs across vehicle types. Significant differences between countries are found in the variability of infrastructure wear and tear costs to levels of traffic. The resulting derived marginal cost also differ widely. The paper provides possible reasons for these differences but recognises that the understanding of the interface between wheel and rail and hence knowledge of cost causation remains fairly limited. The findings of the paper therefore need to be read in the context of further research being required into railway infrastructure cost causation.